Cross-Sectional and Longitudinal Associations of Serum LRG1 with Severity and Prognosis Among Adult Community-Acquired Pneumonia Patients - Wang Y; Jiang Y; Xie M; Qi B; Pu K; Du W; Zhang Q; Ma M; Chen Z; Guo Y; Qian H; Wang K; et al. (Dove Medical Press, 2024)
Yingli Wang,1,2,* Yalin Jiang,2,* Meiling Xie,1,2,* Bin Qi,2 Kunpeng Pu,2 Wenjie Du,2 Qingqing Zhang,2 Mengmeng Ma,2 Ziyong Chen,2 Yongxia Guo,2 Hui Qian,2 Kaiqin Wang,2 Tulei Tian,2 Lin Fu,3 Xiaofei Zhang2 1Bengbu Medical University Graduate School, Bengbu, Anhui, People's Republic of China; 2Department of Respiratory and Critical Care Medicine, The Affiliated Bozhou Hospital of Anhui Medical University, Bozhou, Anhui, People's Republic of China; 3Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of China*These authors contributed equally to this workCorrespondence: Lin Fu, Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230601, People's Republic of China, Tel +86 551 6516 7923, Email fulindev@126.com Xiaofei Zhang, Department of Respiratory and Critical Care Medicine, The Affiliated Bozhou Hospital of Anhui Medical University, Bozhou, Anhui, 236800, People's Republic of China, Email zhangxiaofeibz@163.comBackground: Leucine-rich α-2 glycoprotein 1 (LRG1) is associated with various inflammatory lung diseases. Nevertheless, the connection between LRG1 and adult community-acquired pneumonia (CAP) individuals was still not well understood. Through a prospective cohort study, the correlations of serum LRG1 with severity and prognosis were evaluated in CAP patients.Methods: The study encompassed 327 patients who received the diagnosis of CAP. We collected fasting venous blood and clinical features. Serum LRG1 was detected by ELISA. CAP severity was assessed using various scoring systems. The prognostic outcomes were observed through follow-up visits.Results: The level of serum LRG1 at admission was gradually increased with CAP severity scores. Serum LRG1 level shown positive associations with inflammatory indices, including C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6). Linear and logistic regression analyses suggested that serum LRG1 at admission was positively associated with severity scores and the risk of death in CAP patients. Serum LRG1 in combination with CAP severity scores significantly increased the predictive powers for severity and death compared with single serum LRG1 or severity scores.Conclusion: The study revealed positive connections of serum LRG1 levels with severity and poor prognosis in CAP patients, suggesting LRG1 partakes into the physiological processes of CAP. Serum LRG1 may be regarded as a potential biomarker in predicting the severity and death among CAP patients.Keywords: community-acquired pneumonia, LRG1, severity, outcomes, cohort study